Diagnostic dilemma in catching anaemia early - Debjyoti Mohapatra; Vikas Bhatia; Swayam Pragyan Parida (Wolters Kluwer Medknow Publications, 2018)
Anaemia is major health problem in our country and the foremost cause of disability. The non-specific clinical signs together with lack of knowledge among people are a hindrance for people seeking early care for this disease. Palmar pallor in children for diagnosing anaemia is anaemia has shown to have low sensitivity. Laboratory estimation of haemoglobin levels still are the diagnostic modality of choice in most primary care settings. There are numerous methods based on different principles to estimate haemoglobin. Each method has its own merit and demerit and has to be used appropriately based on that. Some methods like Hemoglobin colour scale have shown have good result to replace Sahli's method but more validation is required. HemoCue also can be used for secondary and tertiary care health institution. A strong political commitment and dedication is required for overcoming operational issues in early diagnosis of anaemia.